Pemodelan Dan Analisa Produksi Kerupuk Subur Dengan Menggunakan Aljabar-Max-Plus - Savina, Dessy Agustin; Saputra, Rika Ardiansyah; Andy Rudhito, Marcellinus (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to model and analyze the optimal time from the time of the cracker production process from the beginning to completion using the Max-Plus algebraic approach at the cracker factory. The study was conducted by collecting data from the field, following the diagram of the production process, modeling mathematically using the Max-Plus algebra, and conducting a simulation calculation using the Scilab program. The results showed that the production process could be required in the Max-Plus algebra matrix equation. The results also showed that the production of cracker crackers can be done periodically, taking about 590 minutes per unit, or about 10 hours in total to complete one production unit. If it is adjusted to the factory work schedule that runs from 05.00 WIB to 15.00 WIB, then 1 production unit can be completed in 1 day, while 10 units require 4 days. Keywords: : Linear System, Algebra Max-Plus, Production System